HUBUNGAN KESEJAHTERAAN PSIKOLOGIS DENGAN TINGKAT STRES DALAM PEMBELAJARAN HYBRID DI UNIVERSITAS HARAPAN BANGSA - Nisa, Nuria Kholifatun; Apriliyani, Ita; Yunida Triana, Noor (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Many students experience various difficulties in doing assignments during hybrid learning. Psychological disorders experienced by students can have an impact on various aspects of college life. Psychological well-being problems can make a student experience affective changes that interfere with daily activities, lose interest in doing daily activities including learning activities, the ability to focus attention becomes impaired, stress, memory ability is impaired, difficulty making decisions, loss of motivation. The purpose of this study was to determine the relationship between psychological well-being and stress levels in nursing students in hybrid learning at Harapan Bangsa University. This study used a descriptive correlative design with a cross sectional approach. The sample of this study amounted to 106 respondents with cluster sampling technique, data analysis using Spearman Rank test. The results of the analysis using Spearman rank obtained a p value of 0.000 (p <0.05) and a correlation coefficient value of -0.448. There is an unidirectional/negative relationship with a weak level of closeness between psychological well-being and stress levels in nursing students in hybrid learning at Harapan Bangsa University, which means that the higher the psychological well-being, the lower the stress level.